VARIATION OF ERYTHROCYTE BINDING ANTIGEN 175 (EBA-175) REGION III-V GENE FROM PLASMODIUM FALCIPARUM JAYAPURA ISOLATE - Wirajaya, Abirackshaan
Malaria is a disease caused by a protozoan parasite of the Plasmodium species. One of the prevention and therapy efforts is the blood stage vaccine, namely the use of Erythrocite Binding Antigen 175 (EBA-175) as an antigen candidate for vaccine production. EBA-175 region III-V shows a protective response at low antibody concentrations, so that immunization in region III-V is more effective as a vaccine candidate for malaria. Region III on EBA-175 has FCR-3 and CAMP sequences with high polymorphism values. The FCR-3 gene consists of 1462 amino acids and CAMp 1435 amino acids. The 27 amino acid variations are caused by differences in the 423 bp F-fragment (141 amino acids) and 342 bp C-fragment (114 amino acids). Therefore, the aim of this study was to determine the polymorphism region of the EBA-175 gene and determine the variation of its gene to other regions. In this study, the construction of the plasmid PfEBA-175 in Escherichia coli from blood samples of infected patients in Jayapura will be carried out. A total of 32 genome DNA samples were isolated for amplification of the EBA-175 III-V gene using forward primers 5'-GCAAGAAGCAGTTCCTGAGG -3' and reverse 5'- CCCAGAATTTCCCCCCCG -3'. The results of gene amplification showed that 15 samples had nucleotide sequences with a length of ~1500 bp. Then the EBA-175 III-V gene fragment was constructed into the pGEM-T Easy cloning vector to transform E.coli host cells. Then the results of the transformation were carried out by blue-and-white screening, then the success of the ligation was checked by colony PCR. Colonies containing the target gene PfEBA-175 were isolated from plasmids for sequencing to determine the nucleotide base sequence. From the results of the base sequence alignment analysis it is known that there are two kinds of alleles, namely FCR-3 and CAMP. Allele dimorphism analysis results obtained 11.1% FCR-3 strains, 88.9% CAMP strains. The genetic variation test from the sequencing results was compared with isolate data from Jayapura and Timika Papua, Tripura India and Thailand showing genetic similarities in these areas. From the experimental results, it can be concluded that there is a polymorphism area in the EBA-175 III-V gene and has genetic similarities with other regions